2015
DOI: 10.4103/2231-0762.156524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-surgical periodontal therapy on serum lipids and C-reactive protein among hyperlipidemic patients with chronic periodontitis

Abstract: Aim:To evaluate the effect of non-surgical periodontal therapy on plasma lipid levels in hyperlipidemic patients with chronic periodontitis.Materials and Methods:After considering the inclusion and exclusion criteria, 30 hyperlipidemic patients with chronic periodontitis in the age group of 30–70 years, undergoing treatment in Ahmed Gasim Cardiac and Renal transplant Centre in north Sudan were recruited for the study. Patients were randomly assigned to the study and control groups. The study group received non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
(54 reference statements)
1
8
0
Order By: Relevance
“… 34 Inversely, previous studies have shown that the treatment for periodontitis lowers the levels of inflammatory markers. 35 , 36 As such, both UAE and periodontitis are commonly related to persistent inflammation that may lead to vascular endothelial dysfunction. They may also be interrelated bidirectionally and deleteriously affect each other.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Inversely, previous studies have shown that the treatment for periodontitis lowers the levels of inflammatory markers. 35 , 36 As such, both UAE and periodontitis are commonly related to persistent inflammation that may lead to vascular endothelial dysfunction. They may also be interrelated bidirectionally and deleteriously affect each other.…”
Section: Discussionmentioning
confidence: 99%
“…The translocation of bacteria and bacterial products of oral cavity can induce a systemic inflammatory process, characterized by high levels of pro-inflammatory cytokines, including increased levels of CRP ( 4 ). CRP has also been considered a significant risk factor for many systemic diseases, such as cardiovascular disease and type 2 diabetes ( 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between periodontal disease and atherosclerosis has been recognized in epidemiological studies (Lockhart et al 2012 ). Periodontitis can elicit endothelial dysfunction, oxidative stress, and lipid accumulation in the aorta (Abe and Hajishengallis 2013 ; Miyajima et al 2014 ; Brito et al 2013 ); in addition, nonsurgical periodontal therapy (NSPT), scaling and root planing (SRP) primarily, improved lipid status and decreased systemic inflammatory response (Tawfig 2015 ; D’Aiuto et al 2006 ; Hada et al 2015 ). For example, SRP decreased serum tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and C-reaction protein (CRP) levels in chronic periodontitis subjects with stable coronary heart disease (Tawfig 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis can elicit endothelial dysfunction, oxidative stress, and lipid accumulation in the aorta (Abe and Hajishengallis 2013 ; Miyajima et al 2014 ; Brito et al 2013 ); in addition, nonsurgical periodontal therapy (NSPT), scaling and root planing (SRP) primarily, improved lipid status and decreased systemic inflammatory response (Tawfig 2015 ; D’Aiuto et al 2006 ; Hada et al 2015 ). For example, SRP decreased serum tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and C-reaction protein (CRP) levels in chronic periodontitis subjects with stable coronary heart disease (Tawfig 2015 ). Intensive periodontal therapy (SRP followed by the adjunctive use of a locally delivered antimicrobial) reduced systemic inflammatory markers and systolic blood pressure, and improved lipid profiles with subsequent changes in cardiovascular risk (D’Aiuto et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%